PENGARUH PEMBERIAN MADU TERHADAP RESPON NYERI ANAK USIA SEKOLAH YANG DILAKUKAN TINDAKAN INVASIF DI RSUD WATES KULON PROGO - Adesti Ratna Pratiwi; Afi Lutfiyati; Dwi Yati (MEDIA ILMU KESEHATAN, 2016)
Background: Invasive therapy is an unpleasant process especially for children, due to its pain effect. Poor awareness on pain and trauma in children for a long period may cause disadvantage in children's growth and development. One of the non pharmacological pain relief managements in children is glucose intake or other sugar substitutes such as honey which consists of flavonoid to relieve pain. Objective: To identify the influence of honey application on pain response in school-aged children during invasive intervention in Wates Regional General Hospital of Kulon Progo. Method: This study was quasy experiment with post-test and non equivalent control group design. Statistical test applied non-parametric test of Mann Whitney with significance level of a=0,05. Samples were selected through purposive sampling technique, consisted of 34 respondents. The study used pure (100%) honey. Five mililiter of honey was administered two minutes prior to invasive intervention. Result: The result figured out p-value of 0.001 (p<0.05) which indicated that there was an influence of honey application on pain response in school-aged children during invasive intervention in Wates Regional General Hospital of Kulon Progo. Conclusion: Honey had an influence on relieving pain during the invasive intervention in school-aged children. Keywords: Invasive intervention, Pain level, Honey